Randomized controlled trial of a positive affect intervention for methamphetamine users. (1st November 2018) - Carrico, Adam W.; Gόmez, Walter; Jain, Jennifer; Shoptaw, Steven; Discepola, Michael V.; Olem, David; Lagana-Jackson, Justin; Andrews, Rick; Neilands, Torsten B.; Dilworth, Samantha E.; Evans, Jennifer L.; Woods, William J.; et al.
Highlights: Tests the efficacy of an integrative intervention for methamphetamine users. Increases in positive affect and mindfulness support the theoretical model. Promising outcomes highlight the need for further randomized controlled trials. Abstract: Background: Contingency management (CM) is an evidence-based intervention providing rewards in exchange for biomarkers that confirm abstinence from stimulants such as methamphetamine. We tested the efficacy of a positive affect intervention designed to boost the effectiveness of CM with HIV-positive, methamphetamine-using sexual minority men. Methods: This attention-matched, randomized controlled trial of a positive affect intervention delivered during CM was registered onwww.clinicaltrials.gov (NCT01926184). In total, 110 HIV-positive sexual minority men with biologically confirmed, recent methamphetamine use were enrolled. Five individual sessions of a positive affect intervention (n = 55) or an attention-control condition (n = 55) were delivered during three months of CM. Secondary outcomes examined over the 3-month intervention period included: 1) psychological processes relevant to affect regulation (i.e., positive affect, negative affect, and mindfulness); 2) methamphetamine craving; 3) self-reported stimulant use (past 3 months); and 4) cumulative number of urine samples that were non-reactive for stimulants (i.e., methamphetamine and cocaine) during CM. Results: Those randomized to the positive affect intervention reported significant increases in positive affect during individual sessions and increases in mindfulness over the 3-month intervention period. Intervention-related improvements in these psychological processes relevant to affect regulation were paralleled by concurrent decreases in methamphetamine craving and self-reported stimulant use over the 3-month intervention period. Conclusions: Delivering a positive affect intervention may improve affect regulation as well as reduce methamphetamine craving and stimulant use during CM with HIV-positive, methamphetamine-using sexual minority men.